1987
DOI: 10.1210/endo-120-1-198
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropins and Estradiol Stimulate Immunoreactive Insulin-Like Growth Factor-I Production by Porcine Granulosa Cells in Vitro*

Abstract: Previous studies have established the ovarian granulosa cell as a site of insulin-like growth factor-I (IGF-I) secretion and action, suggesting an autocrine function for this peptide in the ovary. To better understand how this putative autocrine system is regulated and its interface with the classic ovarian trophic hormones FSH, LH, and estradiol (E2), we have studied the effects of these hormones on the secretion of immunoreactive IGF-I (iIGF-I) by cultured porcine granulosa cells. Immature granulosa cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(82 citation statements)
references
References 44 publications
4
77
0
1
Order By: Relevance
“…In both rat (Borland etal., 1984 ;Mita etal., 1985 ;Oonk etal., 1987a, b) and pig (Jaillard et al, 1987, present (Hammond et al, 1985;Hsu and Hammond, 1987) and rat (Davoren and Hsueh, 1986) granulosa cells and their purtative male homolog, Sertoli cells from the same species (Ritzen, 1983 ;Tres et al, 1986 ;Smith et al, 1987 ;IChatelain etal., 1987), secrete Sm-C/IGF-I immunoreactivity in the medium. The Sm-C/IGF-I-like peptide purified from rat (Smith etal., 1987) The physiological in vivo significance of the endocrine/paracrine/autocrine role of Sm-C/IGF-I on testicular growth and functions is suggested by the fact that in both humans (Tanner et al, 1975 ;Kulin et al, 1981 ;Laron, 1984) Les LC contiennent des récepteurs spécifiques pour la Sm-C/IGF-1 et pour l'insuline, tandis que les SC contiennent seulement des récepteurs pour la Sm-C/IGF-1.…”
mentioning
confidence: 99%
“…In both rat (Borland etal., 1984 ;Mita etal., 1985 ;Oonk etal., 1987a, b) and pig (Jaillard et al, 1987, present (Hammond et al, 1985;Hsu and Hammond, 1987) and rat (Davoren and Hsueh, 1986) granulosa cells and their purtative male homolog, Sertoli cells from the same species (Ritzen, 1983 ;Tres et al, 1986 ;Smith et al, 1987 ;IChatelain etal., 1987), secrete Sm-C/IGF-I immunoreactivity in the medium. The Sm-C/IGF-I-like peptide purified from rat (Smith etal., 1987) The physiological in vivo significance of the endocrine/paracrine/autocrine role of Sm-C/IGF-I on testicular growth and functions is suggested by the fact that in both humans (Tanner et al, 1975 ;Kulin et al, 1981 ;Laron, 1984) Les LC contiennent des récepteurs spécifiques pour la Sm-C/IGF-1 et pour l'insuline, tandis que les SC contiennent seulement des récepteurs pour la Sm-C/IGF-1.…”
mentioning
confidence: 99%
“…Estradiol was also shown to increase IGF 1 in porcine granulosa cells (Hsu CJ, Hammond, 1987). But in the bovine granulosa cells, it was shown that treatment with anti IGF receptor antibody which effectively blocked the protective effect of IGF 1 against apoptosis, did not prevent the protective effect of estradiol (Quirck et al, 2004).…”
Section: Estradiolmentioning
confidence: 96%
“…EGF, TGFα, and bFGF, as well as their receptors, have been found in the ovary (Hsu and Hammond, 1987;Khan-Dawood, 1987;Kudlow et al, 1987) and shown to inhibit spontaneous onset of apoptotic DNA cleavage in cultured granulosa cells (Tilly et al, 1992a, b). EGF suppression of granulosa cell apoptosis is mediated by the stimulation of progesterone production and the regulation of intracellular free calcium concentration (Luciano et al, 1994).…”
Section: Growth Factorsmentioning
confidence: 99%
“…In (Adashi et al, 1991). Furthermore, these cells can produce specific IGF-binding proteins (IGFBPs) (Hsu and Hammond, 1987;Ramasharma and Li, 1987;Voutilainen and Miller, 1987;Mondschein et al, 1990;Adashi et al, 1991;Stanko et al, 1994). (Koistinen et al, 1990) and that these cells synthesize and secrete IGFBP-1 (Suikkari et al, 1989 Correspondence.…”
mentioning
confidence: 99%
“…Ovarian granulosa cells have been shown to produce insulin-like growth factors I or II (IGF-I, IGF-II) in a number of species including rats, pigs, cows and humans (Adashi et al, 1991). Furthermore, these cells can produce specific IGF-binding proteins (IGFBPs) (Hsu and Hammond, 1987;Ramasharma and Li, 1987; Voutilainen and Miller, 1987;Mondschein et al, 1990;Adashi et al, 1991;Stanko et al, 1994). IGFBP-3 has been purified from pig follicular fluid (Ui et al, 1989), while others found it was present in follicular fluid from both small and large follicles.…”
mentioning
confidence: 99%